Native T1 values identify myocardial changes and stratify disease severity in patients with Duchenne muscular dystrophy. Issue 1 (January 2017) - Olivieri, Laura; Kellman, Peter; McCarter, Robert; Cross, Russell; Hansen, Michael; Spurney, Christopher
Abstract Background Duchenne muscular dystrophy (DMD) is an X-linked, inherited disorder causing dilated cardiomyopathy with variable onset and progression. Currently we lack objective markers of the effect of therapies targeted towards preventing progression of subclinical cardiac disease. Thus, our aim was to compare the ability of native T1 and extracellular volume (ECV) measurements to differentiate risk of myocardial disease in DMD and controls. Methods Twenty boys with DMD and 16 age/gender-matched controls without history predisposing to cardiac fibrosis, but with a clinical indication for cardiovascular magnetic resonance (CMR) evaluation, underwent CMR with contrast. Data points collected include left ventricular ejection fraction (LVEF), left ventricular mass, and presence of late gadolinium enhancement (LGE). Native T1, and ECV regional mapping were obtained using both a modified Look-Locker (MOLLI) and saturation recovery single shot sequence (SASHA) on a 1.5T scanner. Using ordinal logistic regression models, controlling for age and LVEF, LGE-free septal we evaluated the ability native T1 and ECV assessments to differentiate levels of cardiomyopathy. Results Twenty DMD subjects aged 14.4 ± 4 years had an LVEF of 56.3 ± 7.4 %; 12/20 had LGE, all confined to the lateral wall. Sixteen controls aged 16.1 ± 2.2 years had an LVEF 60.4 ± 5.1 % and no LGE. Native T1 and ECV values were significantly higher in the DMD group (p < 0.05) with both MOLLI and SASHA imaging techniques. Native T1 demonstrated a 50 % increase in the ability to predict disease state (control, DMD without fibrosis, DMD with fibrosis). ECV demonstrated only the ability to predict presence of LGE, but could not distinguish between controls and DMD without fibrosis. Conclusions LGE-spared regions of boys with DMD have significantly different native T1 and ECV values compared to controls. Native T1 measurements can identify early changes in DMD patients without the presence of LGE and help predict disease severity more effectively than ECV. Native T1 may be a novel outcome measure for early cardiac therapies in DMD and other cardiomyopathies.